Maternal diabetes and the role of neonatal reticulocyte hemoglobin content as a biomarker of iron status in the perinatal period - Babacheva, Evgeniya; Rallis, Dimitrios; Christou, Helen; Mitsiakos, George; Mikos, Themistoklis; Dampala, Kalliopi; Tsakalidis, Christos; Kioumi, Anna; Goulis, Dimitrios G.; Soubasi, Vasiliki (Frontiers in Endocrinology, 2022)
Aims We aimed to evaluate the effects of maternal diabetes on neonatal iron status, measuring erythrocyte indices including hemoglobin, hematocrit, reticulocytes, mean corpuscular volume (MCV), percent (%) hypochromia, ferritin, and additionally mean reticulocyte hemoglobin content (MCHr) as an early marker of iron deficiency, and examine the association between neonatal MCHr, red cell indices, and ferritin. Materials and Methods We conducted a hospital-based prospective cohort study in a tertiary neonatal unit of a University Hospital from 2018 to 2020. We enrolled 126 maternal-infant pairs of mothers whose pregnancy was associated with diabetes and 74 maternal-infant pairs from uncomplicated pregnancies. Erythrocyte indices were analyzed within the first twelve hours after birth. Erythrocyte parameters were compared between infants of the diabetes and the non-diabetic group. We examined the correlation of the neonatal MCHr with perinatal characteristics, including gestation, birth weight, maternal body mass index, the erythrocytic indices, maternal diabetes, maternal obesity, prematurity, small-for-gestational-age status, maternal preeclampsia, and maternal anemia. Finally, we evaluated the discordance between neonatal MCHr and neonatal ferritin. Results Infants of the diabetes group had a significantly lower MCHr (32.6 pg vs. 34.2 pg, p=0.003) compared with infants of uncomplicated pregnancies. Neonatal MCHr was significantly correlated with maternal hypochromia (r=-0.237, p=0.004) and neonatal MCV (r=0.674, p<0.001). Neonatal MCHr was significantly associated with maternal diabetes [standardized coefficients 0.21, 95% confidence interval (CI) 0.05-0.58, p=0.003) and maternal preeclampsia (standardized coefficients 0.17, 95% CI 0.02-0.92, p=0.019), after adjusting for maternal anemia, maternal obesity, prematurity, and small-for-gestational-age status. Those results were consistent also when analyzing maternal-infant pairs with pre-existing diabetes, and maternal-infant pairs with gestational diabetes. There was significant discordance between neonatal MCHr and neonatal ferritin (p=0.001). Conclusions MCHr was significantly lower in infants of mothers whose pregnancy was associated with diabetes compared with infants of non-diabetic mothers and correlated with neonatal and maternal red cell indices of iron deficiency. Since there was significant discordance between neonatal MCHr and ferritin during the first postnatal day, it is possible that MCHr could be used as a screening test for iron deficiency, especially in infants.